Psychosocial Risks: Is Risk Management Strategic Enough in Business and Policy Making? - Melissa K. Langenhan; Stavroula Leka; Aditya Jain (Elsevier, 2013)
Background: In times of continuous change and volatile markets, organizations are increasingly characterized by downsizing, work intensification, and resource rationalization. This has resulted in diversification, and the emergence of new risks within the field of occupational health and safety, with an important impact. This paper focuses on one such type of risk in the modern workplace-psychosocial risks. The current study aimed to explore stakeholder perspectives, regarding the extent to which psychosocial risks are incorporated into strategic risk management practices, at both the business and policy level. Methods: Semi-structured interviews were conducted with 14 professionals, representing employer, expert, policy maker, and trade union stakeholder perspectives. Results: It was found that the majority of organizations do not sufficiently, if at all, understand and incorporate psychosocial risks into strategic decision making, whereby the key barrier related to practical difficulties of not knowing how to manage psychosocial risks adequately. Conclusion: The study found that there is a need to close the gap between policy and practice on a number of levels. Future recommendations comprise a policy framework and infrastructure underpinned by educational initiatives, partnerships, and networks to drive a shift in attitudes toward recognizing the duality of the concept of risk (including both potential negative and positive outcomes) and moving beyond simple regulatory compliance.